Trust in organisations. - Guy Diedrich (2013)
This thesis seeks to contribute to the organisational trust literature by investigating the relevance of trust to organisations through executive self-reports, and exploring the potential congruities and incongruities of these self-reports with the existing trust literature. Further, the study allows for the participants to introduce unique conceptualisations of trust in organisations that may not appear in the literature but might be worthy of further consideration and research. The results of this study begin to fill an existing gap in the trust literature by considering the perceptions of the most senior executives in the corporate environment. A trust typology is proposed (Chapter 5) which distinguishes between characteristics of genuine trust and surrogate trust. Definitions widely cited in the literature are analysed against the typology, and the executives' definitions are compared to consider congruities and incongruities of definitions. The dynamics of trust are examined (Chapter 6), and an optimal trust path for transactions is proposed (Chapter 7). The possible economic impacts of trust in organisations are evaluated (Chapter 8) and new conceptualisations from executive reports are analysed. The extensive use of metaphors by the executives to convey trust is examined (Chapter 9). Alternative configurations of trust are examined (Chapter 10) and a model for optimal trust transactions based on the literature and executive reports are presented. The final chapter argues that future studies may benefit from the findings of this thesis, including key considerations in defining trust for research in organisations, recognising that executives may view trust as an asset that is strategically invested like any other corporate asset, expanding the scope of trust and its potential economic impacts on the organisation, and developing new models for building trust.